Inventory of damage to coral reefs ecosystem in waters of Bungkutoko Island, Kendari City and Barrang Lompo Island, Makassar City - Mosriula; Jaya; Muhammad Hamsir (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2018)
Coastal areas and sea have the potential biological resources large enough, because supported by three main ecosystem the ecosystem mangrove, seagrass beds and coral reefs. To maintain the existence of the ecosystem, control in coastal areas need to conducted one of them is inventory damage ecosystem especially ecosystem coral reefs. On the island of Bungkutoko lack or information on the coral reefs ecosystem is the island Barrang Lompo in addition the information and data on the ecosystem.  The purpose of this research is to get data teachers’ marital status and a condition of damage the ecosystem to coral reefs as a second the island. The research results obtained, a covering of coral reef island Bungkutoko depth 5m and 10m namely 36,47% and 41,67% category ‘being’. The island Barrang Lompo station 1 the depth of 5m and 10m namely 38,67% and 42,53% category ‘being’, station 2  covering 23,27% category ‘broken’. To scattery if coral reefs Bungkutoko island 231.31 ha, the Barrang Lompo island 127.47 ha. The level of damage/index mortalities on the island of Bungkutoko depth 5m and 10m namely 0,5593% and 0,6201% category ‘being’. The island Barrang Lompo station 1 depth 5m and 10m namely 0,6011% and 0,5504% category ‘being’, station 2 the level of damage/index mortalities 0,7326% category ‘high’.